THE IMPACT OF FINANCIAL LITERACY, QUALITY OF LIFE, SOCIOECONOMIC STATUS ON THE CONSUMPTION BEHAVIOR OF PRE-SERVICE TEACHER STUDENTS - Kurniawan, Tito; Farizhi, Muhammad Reza; Setiawan, Ananda (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
This study aims to construct a structural model of the consumption behavior of students of the Teaching and Education Faculty (FKIP) of Universitas Lambung Mangkurat. This study was described using a quantitative method with SEM-PLS to find out the phenomena studied by the decision questionnaire from the questionnaire that had been used in previous studies. The questionnaire was filled in by 214 people from 7810 active students class 2017-2022 FKIP Universitas Lambung Mangkurat by taking data in the form of random sampling. Research shows that financial literacy, quality of life, and social status of parents can be said to be very influential and significant together with the variable knowledge of consumptive behavior of FKIP students at Universitas Lambung Mangkurat.